SYNTHESIS, STRUCTURAL ELUCIDATION, CATALYTIC, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF THIOPHENE DERIVED MIXED LIGAND METAL COMPLEXES - Vairalakshmi, M.; Princess, R.; Kokila Rani, B.; Johnson Raja, S. (Journal of the Chilean Chemical Society, 2018)
The hexa-coordinated mixed ligand Cu(II), Zn(II), Ni(II) and Co(II) complexes of the type [MLX]Cl2 where X=1,10-phenonthroline and ligand (L) have been synthesised from the condensation of thiophene-2-carboxaldehyde with o-phenylenediamine. They were characterised by elemental analysis, molar conductance, magnetic susceptibility, infrared, electronic absorption, proton magnetic resonance and mass spectral studies. An octahedral geometry has been proposed for all these complexes. The high molar conductance studies of the complexes show their electrolytic nature. The infrared spectra of the complexes show that the imine group of the Schiff base coordinate with the metal ion. The electronic absorption spectra of the complexes show the charge transfer, d-d transitions consistent with their proposed geometry. The proton magnetic resonance spectrum of the ligand shows the presence of CH=N group in the ligand. The mass spectral data also confirms the proposed structure of ligand and its complexes. The mixed ligand complexes possess good catalytic activity in the reaction of oxidation of alcohols using H2O2 as oxidant. The antibacterial activity of the mixed ligand complexes has been carried out by disc diffusion method. Copper (II) complexes exhibit potent antibacterial activity when compared to the standard drug streptomycin. The above complexes also exhibited DPPH radical scavenging activity.